Purificação e caracterização parcial de duas N-acetil-ß-hexosaminidases do Equinoderma marinho Echinometra lucunter - Lima, Ádila Lorena Morais (2006)
Two b-N-acetylhexosaminidases (F11 e F15) were purified from Echinometra lucunter gonads extracts. The purified enzymes were obtained using ammonium sulfate fractionation, followed by gel filtration chromatographies (Sephacryl S-200, Sephadex G-75 and Sephacryl S-200). The F11 fraction was purified 192.47 -fold with a 28.5% yield, and F15 fraction 85.41 -fold with a 32.3% yield. The molecular weights of the fractions were 116 kDa for F11 and 42 kDa for F15 using SDS-PAGE. In Sephacryl S-200, F15 was 84 kDa, indicating that it is a dimeric protein. When p-nitrophenyl-β-D-glycosaminide was used as substrate, we determined an apparent Km of 0.257 mM and Vmax of 0.704 for F11 and for F15 the Km was 0.235 mM and Vmax of 0.9 mM of product liberated by hour. Both enzymes have optimum pH and temperature respectively at 5.0 and 45 °C. The enzymes showed inhibition by silver nitrate, while the glucuronic acid was a potent activator. The high inhibition of F15 by N-etylmaleimide indicates that sulphydril groups are involved in the catalysis of synthetic substrate